Learning from student experience: large, higher education classes transitioning online. Issue 2 (3rd April 2021) - Buckley, Karen; Stone, Suzanne; Farrell, Ann Marie; Glynn, Mark; Lowney, Rob; Smyth, Seán
Abstract : In March 2020, Irish universities closed their doors and teaching, learning and assessment moved online, due to the Covid-19 pandemic. This paper arises from a Dublin City University (DCU) research study with a three-fold purpose: Examine the sudden transition of large classes (100+ students) from face-to-face teaching and learning to remote online provision from the perspectives of staff and students. Contextualise these perspectives by reviewing relevant literature. Inform the work of teaching large classes in future online teaching and learning spaces. Presented here, are findings informed by; a rapid, systematised literature review; analysis of student and staff survey responses who experienced the swift move online; and academic support data mined by the Teaching Enhancement Unit (TEU) between March and June 2020. This paper will contribute to prompt, timely reflection on the lived student experience of engagement and isolation during the sudden pivot for large class cohorts. These reflections and analysis will add to the growing body of literature on large class teaching and online pedagogy, specifically in the context of the Covid-19 pandemic. The authors provide conceptualised solutions as we move out of the emergency pivot and into more considered, planned approaches to better engage students in online, hybrid and face-to-face contexts.